Relationship Management and Market Performance of Micro, Small and Medium Enterprises in Wakiso District, Uganda - Henry Stanley Mbowa; Marus Eton; Alice Ngele Mwazuna (Journal of Digital Business and Marketing, 2026)
Purpose: The study examined the influence of relationship management on market performance of MSMEs in Wakiso district. Research Methodology: The study employed cross-sectional design utilizing convergent/concurrent mixed methods approach. A sample of 340 respondents was determined from 2,279 employees using Yamane. Purposive and random were employed to select proprietors and employees respectively. Data was collected through interviews and questionnaires. Quantitative data was analyzed using SPSS v.16.0 and JASP whereas NVivo for qualitative Results: Results indicated that relationship management had a positive but not statistically significant effect on the market performance of MSMEs in Wakiso District (?=1.410; p>0.230). Qualitatively, results indicate that practical importance of relationship management activities is key for customer engagement and business development hance, influencing market performance. Conclusions: The study concluded that although relationship management is crucial, but alone might not influence market performance except combined with other potential marketing strategies. The study recommended that MSMEs should regularly follow-up their customers, integrate non-digital marketing strategies, and invest in relationship management. Limitations: The study employed JASP-SEM to test the moderating effect of the other variables. Thus, poor model specification might lead to underestimation and/or overestimation of the moderation effect. Therefore, this calls for a precise model specification to aid in the test, interpretation and analysis of the results. Contributions: This research provides valuable insights into the role of relationship management in MSMEs’ market performance, offering practical recommendations for integrating both digital and non-digital marketing strategies to enhance customer retention and business growth